ANALISA DAN INTERPRETASI DATA HASIL UJI TAK MERUSAK DALAM RANGKA PENGEMBANGAN BASIS DATA POTENSI CACAT PADA PELET UO2 - Artika, Refa; Fauzi Rahmatullah, Helmi; Gigih Wicaksono, Yusuf; Ismarwanti, Sri; Sigit, Rohmad (Urania: Jurnal Ilmiah Daur Bahan Bakar Nuklir, 2024)
The development of nuclear fuel for both research and power reactors has been the focus of Research Center for Nuclear Fuel Cycle and Radioactive Waste Technology (PRTDBBNLR) research from fabrication, pre-irradiation, irradiation, and post-irradiation examination phases. As the only post-irradiation examination facility in Southeast Asia, Radiometallurgy Installation (IRM) is required to be ready to evaluate the performance of nuclear fuel, one of them is the short pin PWR-fuel containing UO2 pellets which is currently in the irradiation process. One of the efforts made by IRM is to develop non-destructive testing techniques, including methods, analysis, interpretation, and inventory of potential defects that may occur systematically in short pin PWR-fuel containing UO2 pellets. The aim of this research is to inventory methods and data of potential defects in UO2 pellets for a post-irradiation examination database. Characterization was performed on five samples of pre-irradiated UO2 pellets with variations in sintered/raw, good/defect conditions, and differences in uranium enrichment (3%, 4%, and 5%) using visual test methods and digital X-ray radiography. Visual examination can provide interpretation results regarding the conditions on the surface of the UO2 pellets. Digital X-ray radiography was operated at a voltage of 150 kV and a current of 1800 µA to produce a digital image then be carried out an image enhancement process using an image processor to interpret the UO2 pellets. Digital X-ray radiography method and image enhancement process adds information of UO2 pellets data. Cracks and surface holes of UO2 pellets can be mapped. The difference in uranium enrichment can be observed from the gray value graphic. Information from this interpretation will be useful as an initial database of interpretation methods to determine the condition of the UO2 pellets in the irradiated short pin PWR-fuel.